IMPLEMENTING EDUCAPLAY AS A GAME-BASED LEARNING TOOL TO INCREASE STUDENTS’ INTEREST IN LEARNING ENGLISH: A QUANTITATIVE STUDY AT SMKN 1 MAKASSAR - Adsan Fauzan; Syarifuddin Dollah; Ahmad Talib (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2026)
This research aims to investigate the implementation of Educaplay as a Game-Based Learning (GBL) tool to increase students’ interest in learning English at SMK Negeri 1 Makassar. The study employed a quantitative approach with a one-group pretest-posttest design involving 30 eleventh-grade students who have undergone cluster random sampling technique. Data were collected through a questionnaire measuring four indicators of interest: excitement, curiosity, enjoyment, and attention. The results indicate an increase in the mean score, from 43.83 on the pre-questionnaire to 45.57 on the post-questionnaire. However, the paired t-test results show a values of 0.090, which is greater than 0.05, indicating insufficient evidence to reject the null hypothesis (H0). Additionally, the N-gain score of 0.11 falls into within the low category (g < 0.30). these findings indicate that the implementation of Educaplay as a GBL tool is not statistically significant in enhancing students’ interest in learning English.Keywords: Educaplay, Game-Based Learning, students’ interest, English learning